Development of Geopolymer Systems for High Temperature Applications - Vickers, Les (Curtin University, 2015)
Geopolymers are amorphous, inorganic structures based on silicate and aluminate tetrahedrons and could be beneficial in thermal and fire resistant applications. The outcomes from this work suggest that fly ash geopolymer composites suitable for thermal applications can be produced. When compared to OPC based systems geopolymers showed extended thermal resistance (from 500 °C to 800 °C). Improved thermal properties were achieved with increases in compressive strength after firing to 1000 °C and the near elimination of expansive events at high temperature.